A naturopathic treatment approach for mild and moderate COVID-19: A retrospective chart review - Melissa S. Barber; Richard Barrett; Ryan D. Bradley; Erin Walker (Elsevier, 2021)
Objectives: The coronavirus disease 2019 (COVID-19) pandemic has led to significant morbidity and mortality. Although COVID-19 vaccination is available, therapeutic options are still needed. The goal of the present manuscript is to report on a treatment strategy used in a naturopathic medical practice for mild and moderate COVID-19. Design: A retrospective chart review was conducted of 30 consecutive patients diagnosed with mild and moderate COVID-19 who were provided multi-nutrient, herbal, and probiotic treatment in a rural, out-patient, naturopathic primary care setting. Main outcomes measures: The primary outcome was treatment safety; secondary outcomes included changes in symptoms, progression to severe COVID-19, incidence of long COVID, and recovery time. Results: No side effects or adverse events were reported from treatment and all patients experienced resolution of symptoms presumed to be associated with COVID-19 infection. One patient who had been ill for 28 days prior to presentation was hospitalized. Five patients had an illness duration of more than one month. Time to treatment was correlated with duration of illness post-treatment (r = 0.63, p < 0.001) and more symptoms at presentation was correlated with a longer duration of illness (r = 0.52, p < 0.01). Conclusions: In this retrospective chart review, a multi-nutrient, herbal, and probiotic therapeutic approach for mild and moderate COVID-19 appeared to be well-tolerated. Delay in seeking treatment after symptom onset, as well as more symptoms at presentation, were correlated with a longer duration of illness. This treatment strategy may have clinical benefit, warranting prospective clinical trials with confirmed COVID-19 cases.